Local and regional control of calcium dynamics in the pancreatic islet. (September 2017) - Rutter, Guy A.; Hodson, David J.; Chabosseau, Pauline; Haythorne, Elizabeth; Pullen, Timothy J.; Leclerc, Isabelle
Abstract : Ca 2+ is the key intracellular regulator of insulin secretion, acting in the β‐cell as the ultimate trigger for exocytosis. In response to high glucose, ATP‐sensitive K + channel closure and plasma membrane depolarization engage a sophisticated machinery to drive pulsatile cytosolic Ca 2+ changes. Voltage‐gated Ca 2+ channels, Ca 2+ ‐activated K + channels and Na + /Ca 2+ exchange all play important roles. The use of targeted Ca 2+ probes has revealed that during each cytosolic Ca 2+ pulse, uptake of Ca 2+ by mitochondria, endoplasmic reticulum (ER), secretory granules and lysosomes fine‐tune cytosolic Ca 2+ dynamics and control organellar function. For example, changes in the expression of the Ca 2+ ‐binding protein Sorcin appear to provide a link between ER Ca 2+ levels and ER stress, affecting β‐cell function and survival. Across the islet, intercellular communication between highly interconnected "hubs, " which act as pacemaker β‐cells, and subservient "followers, " ensures efficient insulin secretion. Loss of connectivity is seen after the deletion of genes associated with type 2 diabetes (T2D) and follows metabolic and inflammatory insults that characterize this disease. Hubs, which typically comprise 1%‐10% of total β‐cells, are repurposed for their specialized role by expression of high glucokinase ( Gck ) but lower Pdx1 and Nkx6.1 levels. Single cell‐omics are poised to provide a deeper understanding of the nature of these cells and of the networks through which they communicate. New insights into the control of both the intra‐ and intercellular Ca 2+ dynamics may thus shed light on T2D pathology and provide novel opportunities for therapy.